The valuation of the city of Dublin - Dawson, Charles (Statistical and Social Inquiry Society of Ireland, 1897)
As an introduction to the question of the state of the valuation of the city of Dublin, I should wish to refer briefly to the work achieved by the Municipal Corporation since the passing of the Public Health Act of 1878. No one whose memory goes back twenty years can forget the state of the principal streets of the city at that time, composed of inferior paving stones or macadam, in summer they were dust heaps, and in winter seas of mud. On new paving since the date mentioned over #345,000 has been spent.
Read Tuesday, 23rd March, 1897
Keywords: Urban development; Dublin valuation; 314.15